Demographic Study of Female Victims of Sexual Violence Referred to Forensic Medicine in Fars Province - Vaziri, F.; Ghodrati, F.; Saadatmand, N.; Zarenezhad, M.; Foruhari, S.; Akbarzadeh, M. (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the clients’ profile of referred in female victims of sexual violence. Methods: In a period of 7 years (2006-2012), 2113 cases of plaintiffs complaining about women sexual violence were investigated by a questionnaire after receiving permission from Shiraz University of Medical Sciences and Forensic Medicine Organization. Data were analyzed after entering SPSS software, version 16, using descriptive statistics and chi-square. Results: The prevalence of rape has decreased in different ages. In 1668 cases, the plaintiffs were female (78.93 %) and most of the victims (36.5%) aged between 16 and 25 years old. According to Fisher test, there was a significant relationship between the age of the victims and different years of examination (p≤0.001). The highest frequency of 30% is reported at elementary education level. The highest frequency of sexual violence against women (18.3%) was reported in 2006 followed by 18.2% in 2011. In terms of occupation, the highest frequency of victims was related to students estimated as 40.52%. Conclusions: Because of the unpleasant nature of sexual violence, there is a serious need for urgent and necessary consideration of its harmful effects and root out this social dilemma by policy makers. Sexual abuse must be prevented especially using religious achievements or by developing effective control strategies detected and by experience female health care users treated.